Candidates for June 8, 1976 Direct Primary Election Member of the Assembly 36th District - March Fong Eu:::Secretary of State, California::: (1976)
A letter sent from the Secretary of State March Fong Eu supplying a list of candidates for the 36th District Assembly seat. Includes each candidates address, occupation, and political party.